2015
DOI: 10.1039/c5dt01522g
|View full text |Cite
|
Sign up to set email alerts
|

Covalent bridging of surface functionalized Fe3O4 and YPO4:Eu nanostructures for simultaneous imaging and therapy

Abstract: Magnetic luminescent hybrid nanostructures (MLHN) have received a great deal of attention due to their potential biomedical applications such as thermal therapy, magnetic resonance imaging, drug delivery and intracellular imaging. We report the development of bifunctional Fe3O4 decorated YPO4:Eu hybrid nanostructures by covalent bridging of carboxyl PEGylated Fe3O4 and amine functionalized YPO4:Eu particles. The surface functionalization of individual nanoparticulates as well as their successful conjugation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…For protein targeting, YPO 4 :Tb 3+ nanoparticles were subjected to further surface functionalization. First, amine groups were introduced on the particle surface via silanization ((3‐Aminopropyl)triethoxysilane, APTES) [ 29 ] (yielding YPO 4 :Tb 3+ ‐APTES), followed by the coupling of folic acid (FA) using EDC/NHS chemistry [ 26 ] (yielding YPO 4 :Tb 3+ ‐FA) ( Figure a; Scheme S1, Supporting Information). The surface functionalization was confirmed via Fourier Transform Infrared spectroscopy (FTIR) and elemental analysis (carbon‐nitrogen‐hydrogen, CHN).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For protein targeting, YPO 4 :Tb 3+ nanoparticles were subjected to further surface functionalization. First, amine groups were introduced on the particle surface via silanization ((3‐Aminopropyl)triethoxysilane, APTES) [ 29 ] (yielding YPO 4 :Tb 3+ ‐APTES), followed by the coupling of folic acid (FA) using EDC/NHS chemistry [ 26 ] (yielding YPO 4 :Tb 3+ ‐FA) ( Figure a; Scheme S1, Supporting Information). The surface functionalization was confirmed via Fourier Transform Infrared spectroscopy (FTIR) and elemental analysis (carbon‐nitrogen‐hydrogen, CHN).…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR spectrum of unfunctionalized nanoparticles shows an intense double‐peak around 1000 cm −1 , corresponding to phosphate groups (Figure 2b). [ 29 ] The spectrum also indicates the presence of adsorbed solvent molecules on the surface indicated by peaks corresponding to CH 2  (2950 cm −1 ) and OH bonds (3100–3400 cm −1 ). Due to the overlap of the phosphate peak with the SiO peak, no major alterations in the FTIR spectrum were detectable upon APTES modification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amine groups linked to the YPO4: Eu NPs couple with carboxyl groups in the PEGylated iron oxide particles which make up the hybrid nanostructures. Barick et al proved that the magnetic field induced by alternating current can cause self‐heating of these hybrid particles at highly specific absorption rates which enables us to control the therapy while imaging 93. Just the SPIONs have a good heating capacity of about 500 W g −1 Fe in alternating magnetic field of particular conditions of frequency.…”
Section: Functionalization To Enhance Intraoperative Therapiesmentioning
confidence: 99%
“…The previous investigation results indicated that nanosized GdVO 4 :Ln 3+ phosphors have a significant application in a high definition flat display panels and potential applications in biology [16,17,18,19]. Compared with Ln 3+ -activated YVO 4 , GdVO 4 :Ln 3+ exhibits highly efficient emitting phosphors, in which the energy transfers from the GdVO 4 host to the incorporated Ln 3+ ions through V 5+ –O 2− charge transfer (CT), yielding an efficient luminescence of Ln 3+ activators.…”
Section: Introductionmentioning
confidence: 99%